Book Review: Asia Tenggara Masa Modern Awal - NFN Jamaluddin (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2015)
A book written by Reid, Charting the Shape of Early Modern Southeast Asia, examines the period of the early stages of modern history of Southeast Asia from the 15th century until the 17th century. The issues raised are trade and capitalism in Southeast Asia. In this book, Reid uses